2016
DOI: 10.1038/onc.2016.152
|View full text |Cite
|
Sign up to set email alerts
|

The B-cell tumor promoter Bcl-3 suppresses inflammation-associated colon tumorigenesis in epithelial cells

Abstract: Bcl-3 is an atypical member of the IκB family. It associates with p50/NF-κB1 and p52/NF-κB2 homodimers in nuclei where it modulates transcription in a context-dependent manner. A subset of B cell tumors exhibits recurrent translocations of Bcl-3, resulting in overexpression. Elevated expression without translocations is also observed in various B cell lymphomas and even some solid tumors. Here we investigated the role of Bcl-3 in AOM/DSS-induced colon tumors, a mouse model for colitis-associated colorectal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Histology of DSS-treated colon was scored by a combination of inflammatory cell infiltration (score 0-3) and tissue damage (score 0-3) as previously described. 34 Littermate controls were used in all experiments.…”
Section: Cd3-specific Antibody and Dss Treatmentsmentioning
confidence: 99%
“…Histology of DSS-treated colon was scored by a combination of inflammatory cell infiltration (score 0-3) and tissue damage (score 0-3) as previously described. 34 Littermate controls were used in all experiments.…”
Section: Cd3-specific Antibody and Dss Treatmentsmentioning
confidence: 99%
“…18 Finally, Bcl-3 suppresses inflammation-associated colon tumorigenesis in epithelial cells by dampening tumorigenic NF-κB signaling. 19 Moreover, previously uncovered evidence demonstrated the function of Bcl-3 in pluripotency maintenance. Bcl-3 functions as a downstream molecule of LIF/STAT3 signaling and positively regulates pluripotency genes, including Oct4, Sox2, and Nanog, in mouse embryonic stem cells (mESCs).…”
Section: Introductionmentioning
confidence: 99%
“…6D). Since Tnfα is critical for lupus‐like phenotypes in lpr mice and Bcl‐3 negatively regulates the Tnfα signaling pathways [29], we hypothesized that suppression of Tnfα signaling may be critical for the inhibitory function of Bcl‐3 in restraining autoimmunity in lpr mice. We, thus, generated Bcl‐3, Fas, and Tnfα triple deficient mice, and found that loss of Tnfα attenuated splenomegaly in Bcl3 −/− / lpr mice (Fig.…”
Section: Resultsmentioning
confidence: 99%